Annual Report on the Development of the Indian Ocean Region (2017) The Belt and Road Initiative and South Asia (Research Series on the Chinese Dream and China's Development Path,, 2018)
The report was written by senior scholars of international studies and Indian Ocean studies and focuses on international relations in the Indian Ocean region and covers many aspects of OBOR policy and South Asia. The report includes both a strategic review and major events, as well as related data in this region. This book also includes the origin, the aims, frameworks, the regional and global impact of India's new development under the Modi administration. The book includes the authors from 5 different institutes in China which provide readers with a full and authentic picture of India's most recent development. This year's Annual Report is the fourth of this kind and the only one which covers exclusively the Indian Ocean region in China.